Determination of the critical pressure for a hot-water pipe with a corrosion defect - Kozak, Dražan (Materiali in tehnologije, 2010)
This paper deals with a determination of the critical pressure, i.e., the allowable operating pressure, of a corroded pipeline. This allowable pressure, as well as the safe-working pressure, are determined by using the analytic expressions given in the DNV-RP-F101 procedure for corroded pipelines. The failure pressure was calculated numerically using the finite-element method (FEM) with assumption of linear-elastic and ideal-plastic behaviour of the pipe material.
Keywords: vročevodi; korozija; tlak; finite element method; metoda končnih elementov